Art in motion current research in screendance = Art en mouvement : recherches actuelles en cinâe-danse - Boulegue, Franck; Hayes, Marisa C.; Walon, Sophie; Kappenberg, Claudia; Amprimoz, Clotilde; Glenn, Tim; Herfeld, Stâephanie; Carrot, Marion; Ruiz Carballido, Paulina; Allen, June; Gaal, Mariann; Tropia, Gabriela (Cambridge Scholars Publishing, 2015)
"Composed of papers originally presented during the International Screendance Conference at the Festival International de Video Danse de Bourgogne, 'Art in motion' considers the choreography of moving images from a variety of angles, including somatic camera work, aesthetic and gestural analysis, and historical research that delves into cinema's earliest depictions of dance, as well as perspectives from contemporary screendance artists. The geographic diversity of the contributors, many of whom are translated in English for the first time this volume, reflects the growing number of screendance scholars and artists around the world, providing valuable insights from France, the United Kingdom, Mexico, Brazil, Hungary, and the United States. 'Art in motion' adopts a broad definition of screendance that explores movement on-screen and with the camera in many forms, while citing parallels between other artistic movements and practices that raise important questions about the role of screendance in moving image and choreographic cultures today."--From jacket.